2023
DOI: 10.1007/s12072-023-10549-2
|View full text |Cite
|
Sign up to set email alerts
|

Consensus on the tertiary prevention of primary liver cancer

Abstract: To effectively prevent recurrence, improve the prognosis and increase the survival rate of primary liver cancer (PLC) patients with radical cure, the Chinese Society of Hepatology, Chinese Medical Association, invited clinical experts and methodologists to develop the Consensus on the Tertiary Prevention of Primary Liver Cancer, which was based on the clinical and scientific advances on the risk factors, histopathology, imaging finding, clinical manifestation, and prevention of recurrence of PLC. The purpose i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…Recurrence is consistently a crucial concern in curative treatment for HCC, prompting studies aimed at predicting the likelihood of recurrence. The ERASL model that included over 3000 cases showed that the male sex, ALBI grade, microscopic invasion, AFP, tumor size, and number of lesions could be incorporated to predict the possibility at a cut-off value; furthermore, the model indicated that risk factors could be stratified from low- to high-risk groups [ 19 , 20 , 21 ]. Higher serologic factors, such as AFP and des-γ-carboxyprothrombin (DCP), tumor volume, multiple nodules, microvascular invasion, and poorly differentiated types have been assumed to be aggressive tumor factors.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence is consistently a crucial concern in curative treatment for HCC, prompting studies aimed at predicting the likelihood of recurrence. The ERASL model that included over 3000 cases showed that the male sex, ALBI grade, microscopic invasion, AFP, tumor size, and number of lesions could be incorporated to predict the possibility at a cut-off value; furthermore, the model indicated that risk factors could be stratified from low- to high-risk groups [ 19 , 20 , 21 ]. Higher serologic factors, such as AFP and des-γ-carboxyprothrombin (DCP), tumor volume, multiple nodules, microvascular invasion, and poorly differentiated types have been assumed to be aggressive tumor factors.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria were as follows: [ 1 ] cohort studies; [ 2 ] studies involving adult participants (aged ≥ 18 years); [ 3 ] studies clearly stating liver cancer as the outcome of interest; [ 4 ] studies providing explicit reports on the effect size of serum TC, TG, HDL-C, or LDL-C levels; and [ 5 ] studies reporting effect size measurements as hazard ratios (HRs) or relative risks (RRs) with corresponding 95% confidence intervals (95% CIs).…”
Section: Methodsmentioning
confidence: 99%
“…The exclusion criteria were as follows: [ 1 ] study design: studies with small sample sizes or significant selection bias; [ 2 ] age range: studies that did not cover the age range of the target participants; [ 3 ] outcome clarity: studies that did not explicitly state the study outcome or relevant indicators; [ 4 ] missing data: studies with substantial missing data or for which valid data could not be obtained; and [ 5 ] duplicate publications: studies that had been previously published in other literature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the poor long-term clinical prognosis of HCC poses a serious public health problem in countries around the world 14 . Therefore, it is particularly necessary to explore the underlying mechanisms of the development of NALFD, liver cirrhosis and HCC, as well as new therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%